Cuprous oxide / carbon nitride composite material as well as preparation method and application thereof
Synthesize oxide copper/nitride composite materials through liquid -phase reduction method and modify it on the glass carbon electrode, solving the problem of complexity and detection performance of composite materials in existing technologies, realizing simplifying preparation, reducing costs, and improving costs Detection performance effect.
Patent Information
- Application Number
- CN202411333237.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-28
AI Technical Summary
In the prior art, the composite material preparation process is too complex, which is not conducive to green mass production, and is not used for biomarker detection. Especially in glucose detection, there are problems such as complex material preparation process, difficulty in cost control and insufficient detection performance.
Synthesize oxide copper/nitride composite materials through liquid -phase reduction method, and use carbonate quantum dots to react with copper salt solution to form a walnut -like copper -like copper/carbon nitride composite particle, and modify it in the glass carbon carbon In the electrode, for electrochemical testing of glucose.
The simplified preparation process has been achieved, the production cost is reduced, the sensitivity and limit of glucose detection are improved, and the electrochemical active area and activity site are enhanced, and the electrocatalytic oxidation performance of glucose is significantly improved.
Smart Images

Figure CN119370880A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of materials and relates to a composite material, in particular to a cuprous oxide / carbon nitride composite material and a preparation method and application thereof. Background Art
[0002] In clinical treatment and diagnosis, it is very important to design sensitive, simple, accurate and instant sensing electrodes to sense and detect glucose.
[0003] Transition metal oxide-based electrochemical sensing electrodes have broad application prospects, especially Cu 2 O, has high electrochemical catalytic activity for biomarkers. However, Cu 2 The low conductivity of O limits its detection performance. Composite with conductive polymers, carbon materials or other semiconductor materials can greatly improve the detection performance of Cu 2 O electrocatalytic activity, improving the detection performance of biomarkers. 3 N 4 ) is an n-type polymer semiconductor with the advantages of excellent chemical stability, good intrinsic electron mobility, low cost, easy availability and photoresponsiveness. It has become one of the most promising materials in fields such as electrochemistry and photocatalysis.
[0004] For example, a layer of Cu is sputtered on the surface of FTO glass, and Cu(OH) is obtained by electroplating oxidation. 2 Nanoarrays, annealed into Cu 2 O nanoarray; and through the centrifugal composite method, C 3 N 4 With Cu 2 O nanoarray composite, and finally sputtered a layer of TiO 2 , forming a multi-level heterojunction, thereby improving the catalytic performance of the photocatalyst; however, the preparation process of the composite material is too complicated, which is not conducive to green mass production, and has not been applied to biomarker detection.
[0005] For example, by applying voltage, Ti 3 C 2 Nanosheets are deposited onto the cathode FTO glass surface and form Ti 3 C 2 Thin film; NH 2 -MIL-125 powder methanol dispersion is added dropwise to Ti 3 C 2 The film surface is dried to constant weight to obtain a photoelectrochemical sensor for detecting glucose with high precision. This invention can detect glucose under the synergistic effect of photoelectricity, but the preparation process of the required materials is complicated, which is not conducive to cost control and large-scale production. Summary of the invention
[0006] The present invention provides a cuprous oxide / carbon nitride composite material and a preparation method, application and electrode to overcome the defects of the prior art.
[0007] To achieve the above object, the present invention adopts the following technical solutions: A method for preparing a cuprous oxide / carbon nitride composite material comprises adding carbon nitride quantum dots into a copper salt solution, and obtaining walnut-shaped cuprous oxide / carbon nitride composite particles with cuprous oxide as the main body and carbon nitride monodispersed on the surface of cuprous oxide by a liquid phase reduction method.
[0008] To optimize the above technical solutions, the specific measures taken also include: Furthermore, the preparation method of the carbon nitride quantum dots is: mixing sodium citrate and urea and grinding them for 0-20 minutes, transferring them to a reactor, heating them at 160-200°C for 1-4 hours, and obtaining carbon nitride quantum dots with a diameter of 1-40 nm; the molar ratio of sodium citrate to urea is 1:40-60.
[0009] Furthermore, the synthesis method of the cuprous oxide / carbon nitride composite particles is as follows: reacting polyvinyl pyrrolidone (PVP) with copper sulfate (CuSO 4 ) add carbon nitride quantum dots to the mixed solution and stir to mix evenly; then add sodium citrate and anhydrous sodium carbonate mixed solution dropwise and continue stirring; then add glucose solution dropwise and continue stirring; finally, heat the mixed solution to obtain the cuprous oxide / carbon nitride composite particles.
[0010] Furthermore, the molar ratio of polyvinyl pyrrolidone, copper sulfate, carbon nitride quantum dots, sodium citrate, anhydrous sodium carbonate and glucose is 0.004~0.006: 0.0003~0.0005: 0.000001~0.0001: 0.00035~0.00135: 0.0005~0.0021: 0.00075~0.003.
[0011] Furthermore, the particle size of the carbon nitride quantum dots is 1 to 40 nm.
[0012] Furthermore, during the synthesis of the cuprous oxide / carbon nitride composite particles, the heating temperature is 60-90° C. and the heating time is 1-4 h.
[0013] Furthermore, during the synthesis of the cuprous oxide / carbon nitride composite particles, a mixed solution of sodium citrate and anhydrous sodium carbonate and a glucose solution are added dropwise and stirred for 1 to 20 minutes.
[0014] The present invention also provides a cuprous oxide / carbon nitride composite material obtained by the above-mentioned preparation method. The particle size of the cuprous oxide / carbon nitride composite particles is 200 nm to 1.2 μm.
[0015] The present invention also provides application of the cuprous oxide / carbon nitride composite material in electrochemical detection of glucose.
[0016] The present invention also provides an electrode for an electrochemical glucose sensor: modified with the above-mentioned cuprous oxide / carbon nitride composite material. Specifically, the cuprous oxide / carbon nitride composite material is ultrasonically mixed with a dimethylformamide (DMF) solution to obtain a uniform composite dispersion, wherein the amount ratio of the cuprous oxide / carbon nitride composite material to the dimethylformamide solution is 1-5 mg: 0.5-2 mL; the composite dispersion is drop-cast onto the surface of a glassy carbon electrode (GCE) and modified multiple times; and then the chitosan aqueous solution is modified to obtain a glassy carbon electrode modified with the cuprous oxide / carbon nitride composite material. The glassy carbon electrode modified with the cuprous oxide / carbon nitride composite material is used as the working electrode, the Pt sheet is used as the counter electrode, and the silver / silver chloride (Ag / AgCl) electrode is used as the reference electrode. The sample to be tested containing glucose is added to a NaOH solution for an amperometric response test, and the voltage is 0.50-0.70 V.
[0017] The present invention also provides the application of the above-mentioned cuprous oxide / carbon nitride composite material in photoelectric cooperative sensing. Specifically, the response of the glassy carbon electrode modified with the cuprous oxide / carbon nitride composite material to glucose is enhanced by applying light. The light wavelength is 200-900 nm, and the light power is 0-20 watts. The working electrode of the glassy carbon electrode modified with the cuprous oxide / carbon nitride composite material has higher electrochemical activity under the addition of light, and can enhance the response to glucose.
[0018] The beneficial effect of the present invention is that the present invention synthesizes carbon nitride quantum dots by high temperature reaction, and then obtains cuprous oxide / carbon nitride composite material by liquid phase reduction method. The composite material is mainly composed of cuprous oxide, and carbon nitride is monodispersed on the surface of cuprous oxide in the form of walnut-like particles with a particle size of about 500 nm. The composite material can be used for electrochemical detection of glucose. Specifically, the walnut-like structure can give the electrode a larger electrochemical active area (0.128 cm 2 ); at the same time, the surface of the walnut-shaped nanoparticles has uniform and dense protrusions, which also provide abundant active sites for the electrocatalytic oxidation of glucose, thereby obtaining a larger current response and having better electrocatalytic glucose performance than pure cuprous oxide; in addition, the composite material is specifically a pn heterojunction structure of n-type semiconductor carbon nitride loaded with p-type semiconductor metal oxide cuprous oxide, which promotes the charge transfer at the interface through photoelectric synergy, and further enhances the detection performance of glucose. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The Cu prepared in Example 1 2 O / C 3 N4 Scanning electron microscopy images of the composite materials.
[0020] Figure 2 The Cu prepared in Example 1 2 O / C 3 N 4 Transmission electron microscopy image of the composite material.
[0021] Figure 3 The Cu prepared in Example 1 2 O / C 3 N 4 X-ray energy spectrum of the composite material, where a is Cu element, b is O element, c is C element, and d is N element; Figure 4 are cyclic voltammograms of different electrodes of Example 2 and Comparative Example 2 in the presence and absence of 0.1 mM glucose in 0.1 M NaOH; Figure 5 is the Cu of Example 2 2 O / C 3 N 4 Current response diagram of GCE sensor electrode at 0.60 V when glucose is continuously added into 0.1 M NaOH; Figure 6 is the Cu of Example 2 2 O / C 3 N 4 The corresponding calibration curve of the GCE sensing electrode to glucose current response; Figure 7 The 365 nm ultraviolet light irradiation Cu in Example 3 2 O / C 3 N 4 Current response diagram of GCE sensor electrode at 0.60 V when glucose is continuously added into 0.1 M NaOH; Figure 8 The 365 nm ultraviolet light irradiation Cu in Example 3 2 O / C 3 N 4 Corresponding calibration curve plot of the GCE sensing electrode to glucose current response. DETAILED DESCRIPTION
[0022] The present invention is further described below in conjunction with specific embodiments.
[0023] Embodiment 1: This embodiment provides a cuprous oxide / carbon nitride composite material, and its preparation method comprises the following steps: Step 1: High temperature heating to synthesize C 3 N 4Quantum dots: 0.081 g of sodium citrate and 0.101 g of urea were mixed and added to a mortar and ground evenly, and heated in a reactor at 180 °C for 2 h. Then, deionized water was washed three times and dried in a vacuum oven at 72 °C for 12 h to obtain C 3 N 4 Quantum dots.
[0024] Step 2: Polyvinyl pyrrolidone (PVP), copper sulfate (CuSO 4 ) and carbon nitride (C 3 N 4 ) quantum dots were added into deionized water to prepare a mixed solution of 0.901 mol / L polyvinyl pyrrolidone, 0.068 mol / L copper sulfate and 0.095 mol / L carbon nitride quantum dots (10 mL). After thorough mixing, 1 mL of a mixed solution of 0.843 mol / L sodium citrate and 1.199 mol / L anhydrous sodium carbonate was added dropwise, and magnetic stirring was performed for 10 min. Then, 1 mL of 1.541 mol / L glucose solution was added dropwise into the above solution. After magnetic stirring for 10 min, the above solution was heated in a water bath at 70 °C for 2 h. Subsequently, deionized cleaning was performed 3 times, and the solution was dried in a vacuum drying oven at 60 °C for 6 h to obtain cuprous oxide / carbon nitride (Cu 2 O / C 3 N 4 ) composite materials.
[0025] Cu 2 O / C 3 N 4 The SEM, TEM and X-ray energy spectrum of the composite materials are shown in Figure 2. Figure 1 , Figure 2 and Figure 3 As shown. Figure 1 and Figure 2 It can be seen that Cu 2 O / C 3 N 4 The composite material is a walnut-shaped spherical particle with a diameter of about 500 nm. The surface of the spherical nanoparticles has uniform and dense protrusions, which can not only increase the electrochemical active area of the electrode when used as a catalytic medium, but also provide abundant active sites for the electrocatalytic oxidation of biomarkers, thereby obtaining a larger current response. Figure 3 Among them, Cu and O elements belong to Cu 2 O, C and N elements belong to C 3 N 4 .Depend on Figure 3It can be seen that the C and N elements are evenly dispersed in the spherical morphology, which further confirms that Cu 2 O was successfully synthesized, and it can be seen that C 3 N 4 Uniformly loaded on Cu 2 O surface.
[0026] Comparative Example 1: This comparative example provides cuprous oxide, and its preparation method is as follows: polyvinyl pyrrolidone and copper sulfate are added to deionized water to prepare 10 mL of a mixed solution with a concentration of 0.901 mol / L polyvinyl pyrrolidone and 0.068 mol / L copper sulfate; after thorough mixing, 1 mL of a mixed solution of 0.843 mol / L sodium citrate and 1.199 mol / L anhydrous sodium carbonate is added dropwise, and magnetic stirring is performed for 10 min; then 1 mL of 1.541 mol / L glucose solution is added dropwise to the above solution, and after magnetic stirring for 10 min, the above solution is heated in a water bath at 70°C for 2 h; then, deionized water is washed 3 times, and vacuum drying is performed, the drying temperature is 60°C, and the drying time is 6 h, to obtain cuprous oxide (Cu 2 O).
[0027] Example 2: This example provides an application of a cuprous oxide / carbon nitride composite material in electrochemical detection of glucose. Specifically, an electrode for an electrochemical glucose sensor is provided, a glassy carbon electrode modified with a cuprous oxide / carbon nitride composite material, and the preparation method thereof is as follows: polishing a glassy carbon electrode (GCE) with alumina powders having particle sizes of 0.5 μm and 0.03 μm, respectively, and ultrasonically washing in anhydrous ethanol and ultrapure water for 10 min, and finally drying with high-purity nitrogen; weighing 2 mgCu 2 O / C 3 N 4 The composite material was mixed with 1 mL of dimethylformamide (DMF) solution by ultrasonication to obtain a uniform Cu 2 O / C 3 N 4 DMF composite dispersion, use a pipette to transfer Cu 2 O / C 3 N 4 The DMF composite dispersion was added dropwise to the surface of the glassy carbon electrode for a total of 3 modifications and dried at room temperature for 6 h. Then 5 μL of 0.5% chitosan aqueous solution was added and dried overnight to obtain Cu 2 O / C 3 N 4 GCE sensing electrode.
[0028] Comparative Example 2: This comparative example provides the application of cuprous oxide in electrochemical detection of glucose. Specifically, it provides an electrode for an electrochemical glucose sensor, a cuprous oxide-modified glassy carbon electrode, and its preparation method is as follows: the glassy carbon electrode is polished with aluminum oxide powders with particle sizes of 0.5 μm and 0.03 μm, respectively, and ultrasonically washed in anhydrous ethanol and ultrapure water for 10 min, and finally dried with high-purity nitrogen. Weigh 2 mg of Cu 2 O, and then mixed it with 1 mL of dimethylformamide solution by ultrasonication to obtain a uniform Cu 2 O DMF composite dispersion, pipette 2.0 µL of Cu 2 The O DMF composite dispersion was added dropwise to the surface of the glassy carbon electrode for a total of 3 modifications and dried at room temperature for 6 h; then 5 μL of 0.5% chitosan aqueous solution was added and dried overnight to obtain Cu 2 O GCE sensing electrode.
[0029] Cu 2 O GCE sensing electrode and Cu 2 O / C 3 N 4 The GCE sensing electrode was used as the working electrode, the Pt sheet (10 × 10 × 0.2 mm) was used as the counter electrode, and the Ag / AgCl electrode was used as the reference electrode at 100 mV s -1 At a scan rate of , Cu 2 OGCE sensing electrode and Cu 2 O / C 3 N 4 The cyclic voltammetric responses of the GCE sensing electrode in 0.1 M NaOH solution with or without 1 mM glucose are shown in Figure 2. Figure 4 shown.
[0030] The results show that Cu 2 The O GCE sensing electrode has an oxidation peak at around 0.45 V in a 0.1 M NaOH solution containing glucose, which corresponds to the oxidation of glucose to gluconic acid. 2 O / C 3 N 4 No obvious oxidation peak was observed for the GCE sensing electrode in 0.1 M NaOH solution without glucose, but an oxidation peak at around 0.42 V was observed in 0.1 M NaOH solution containing glucose, which also corresponds to the process of glucose being oxidized to gluconic acid. In addition, a broad reduction peak at around 0.63 V was observed regardless of the presence of glucose. 2 O / C 3 N 4The GCE sensing electrode has a higher concentration of Cu in the presence of 0.1 M NaOH solution containing glucose. 2 O GCE sensing electrode has a stronger redox current response and thus exhibits a higher performance than pure Cu 2 O-based sensing electrode has higher glucose electrocatalytic activity.
[0031] Cu 2 O / C 3 N 4 The GCE sensing electrode was used as the working electrode, the Pt sheet (10×10×0.2 mm) was used as the counter electrode, and the Ag / AgCl electrode was used as the reference electrode. Glucose was gradually added to the continuously stirred NaOH solution at a working potential of 0.60 V. The change of the current response over time was used to reflect the Cu 2 O / C 3 N 4 The electrocatalytic performance of the GCE sensor electrode to glucose, the change of current response over time is shown in Figure 5 As shown in Figure 2, the linear relationship between current and glucose concentration is as follows: Figure 6 shown.
[0032] from Figure 5 It can be seen that the current intensity increases with the increase of glucose concentration, and the current response trend is relatively stable after the addition of glucose. Figure 6 It can be seen that through linear fitting, it can be found that when the glucose concentration is in the range of 5 µM to 3000 µM, there is a good linear relationship between the response current and the glucose concentration. The linear equation after fitting is I = 339.22 C + 33.56 (I: response current density, C: glucose concentration). After calculation, the detection sensitivity of the sensor electrode is 339.22 µA cm -2 mM -1 The detection limit was 6.55 µM (signal-to-noise ratio S / N = 3).
[0033] Example 3: This example provides an application of cuprous oxide / carbon nitride composite materials in photoelectric synergistic sensing. Specifically, the response of the glassy carbon electrode modified with the cuprous oxide / carbon nitride composite material to glucose is enhanced by applying light, that is, the photoelectric synergistic enhancement of the glucose detection performance of the cuprous oxide / carbon nitride composite material.
[0034] According to Example 2, Cu 2 O / C 3 N 4 The glucose sensor detection system with the GCE sensing electrode as the working electrode verifies its response to light by adding light (ultraviolet) to the surface of the sensor working electrode. The results are as follows: Figure 7 and 8 shown.
[0035] The results show that due to Cu 2 O and C 3 N 4 The formation of a pn-type heterojunction promotes interfacial charge transfer and inhibits the recombination of photogenerated carriers. The synergistic effect of photocatalysis and electrocatalysis significantly improves the electrochemical performance of the sensing electrode. The time-current curve is used to analyze the current response of the electrode to glucose under different illumination frequencies and intensities, as well as in the absence of light ( Figure 5 , Figure 6 ) and ultraviolet light ( Figure 7 , Figure 8 ) under ultraviolet light. After applying ultraviolet light, the electrode's detection performance for glucose was significantly improved, and the sensitivity of glucose detection was increased to 690.38 μA cm −2 mM −1 , the detection limit was reduced to 3.23 μM, and the glucose content in sweat was accurately detected.
[0036] As can be seen from the above, the Cu synthesized by the present invention 2 O / C 3 N 4 The sensing electrode constructed with the composite material as the catalytic medium has high sensitivity to glucose detection and low detection limit, and has excellent performance in glucose detection. It also has good photoelectric synergy, which makes it have better sensing performance for glucose. Therefore, it has great application potential in the field that requires rapid quantitative glucose.
[0037] In the present invention, unless otherwise specified, the scientific and technical terms used herein have the meanings commonly understood by those skilled in the art. In addition, the reagents, materials and operating procedures used herein are reagents, materials and conventional procedures widely used in the corresponding fields.
[0038] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a cuprous oxide / carbon nitride composite material, characterized in that: Carbon nitride quantum dots are added into a copper salt solution, and walnut-shaped cuprous oxide / carbon nitride composite particles are obtained by a liquid phase reduction method, wherein cuprous oxide is the main component and carbon nitride is monodispersed on the surface of cuprous oxide.
2. The method for preparing the cuprous oxide / carbon nitride composite material according to claim 1, characterized in that: The preparation method of the carbon nitride quantum dots is as follows: sodium citrate and urea are mixed and ground for 0-20 min, transferred to a reaction kettle, and heated at 160-200° C. for 1-4 h to obtain carbon nitride quantum dots with a diameter of 1-40 nm; The molar ratio of sodium citrate to urea is 1:40-60.
3. The method for preparing the cuprous oxide / carbon nitride composite material according to claim 1, characterized in that: The synthesis method of the cuprous oxide / carbon nitride composite particles is as follows: adding carbon nitride quantum dots to a mixed solution of polyvinyl pyrrolidone and copper sulfate, stirring and mixing evenly; then adding a mixed solution of sodium citrate and anhydrous sodium carbonate dropwise, continuing to stir; then adding a glucose solution dropwise, continuing to stir; and finally heating the mixed solution to obtain the cuprous oxide / carbon nitride composite particles.
4. The method for preparing the cuprous oxide / carbon nitride composite material according to claim 3, characterized in that: The molar ratio of polyvinyl pyrrolidone, copper sulfate, carbon nitride quantum dots, sodium citrate, anhydrous sodium carbonate and glucose is 0.004-0.006: 0.0003-0.0005: 0.000001-0.0001: 0.00035-0.00135: 0.0005-0.0021: 0.00075-0.
003.
5. The method for preparing the cuprous oxide / carbon nitride composite material according to claim 3, characterized in that: The particle size of carbon nitride quantum dots is 1~40 nm.
6. The method for preparing the cuprous oxide / carbon nitride composite material according to claim 3, characterized in that: During the synthesis of the cuprous oxide / carbon nitride composite particles, the heating temperature is 60-90° C. and the heating time is 1-4 hours.
7. The cuprous oxide / carbon nitride composite material obtained by the preparation method according to any one of claims 1 to 6.
8. Use of the cuprous oxide / carbon nitride composite material as claimed in claim 7 in electrochemical detection of glucose.
9. An electrode for an electrochemical glucose sensor, characterized in that: Modified with the cuprous oxide / carbon nitride composite material as claimed in claim 7.
10. Use of the cuprous oxide / carbon nitride composite material as claimed in claim 7 in photoelectric cooperative sensing.
Citation Information
Cited By
Copper-based nano carbon nitride material, synthesis method and method for electrochemically detecting perfluoro and polyfluoroalkyl compounds by using copper-based nano carbon nitride material
CN120587475A
Cuprous oxide-graphite phase carbon nitride SERS (Surface Enhanced Raman Scattering) enhanced substrate and application thereof in pesticide residue detection
CN120971393A